Effect of Cheddar cheese whey on composition, characteristics and shelf life of bun - Parmar, Satishkumar Chaturbhai; Jain, Amit Kumar (Indian Journal of Dairy Science, 2018)
Abstract Disposal of large quantity of whey is a big task for dairy industry. To exploit ability of whey to improve functionality of bakery products, Cheddar cheese whey (Sweet whey) and Paneer whey (acid whey) were utilized for dough preparation in bun manufacture. Both whey were tested for their compatibility with bun. Based on sensory evaluation, the former was found more suitable in bun. When evaluated for its rate of addition, bun with 75 per cent Cheddar cheese whey has improved crust colour and surface characteristics than control bun (without whey). The incorporation of whey improved the fat, protein and mineral content as well as texture of bun as compared to control bun. The Cheddar cheese whey had no any adverse effect on microbiological quality of the bun. The physical properties of bun like loaf weight, crust colour and crumb colour have been improved by addition of Cheddar cheese whey. During storage, there was no significant difference observed in the volume, crust colour and surface characteristics and crumb colour of the bun prepared with Cheddar cheese whey. No significant change was observed in peroxide value of both the types of bun. However, during the storage period, a significant change in the peroxide values of both the types of bun was evident. Overall, Cheddar cheese whey addition in dough making of bun has improved composition and different characteristics of bun. The incorporation of whey had no any adverse effect on keeping quality of the buns.